2019
DOI: 10.1016/j.ctim.2019.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Tai Chi in Chinese adults with metabolic syndrome: A pilot randomized controlled trial

Abstract: in Chinese adults with metabolic syndrome: A pilot randomized controlled trial. Complementary therapies in medicine, 46, 54-61.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Exercise can improve the overall health and basic life quality of MA dependents (80) and is associated with notable improvements in cardiopulmonary health in individuals using MA (52). This study showed significant differences in systolic blood pressure and vital capacity in the exercise group, which was in accordance with many previous studies (81)(82)(83)(84). TC exerted influence on the activity of parasympathetic nervous system and the sensitivity of baroreceptor, thereby leading to the positive change of blood pressure (85)(86)(87).…”
Section: Improvements In Physical Functionsupporting
confidence: 92%
“…Exercise can improve the overall health and basic life quality of MA dependents (80) and is associated with notable improvements in cardiopulmonary health in individuals using MA (52). This study showed significant differences in systolic blood pressure and vital capacity in the exercise group, which was in accordance with many previous studies (81)(82)(83)(84). TC exerted influence on the activity of parasympathetic nervous system and the sensitivity of baroreceptor, thereby leading to the positive change of blood pressure (85)(86)(87).…”
Section: Improvements In Physical Functionsupporting
confidence: 92%
“…Table 1 summarises the characteristics of the included RCTs. The studies were conducted across 18 countries, including Europe [ 33 , 34 , 36 , 40 , 42 , 43 , 45 , 47 , 48 , 52 , 55 ], USA [ 32 , 35 , 37 39 , 46 , 50 , 54 ], Australia [ 41 ], and Asia [ 44 , 49 , 51 , 53 ]. A total of 18 studies reported the type of recruitment strategy used with 50% using a mix of both direct (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly applied type of exercise therapy was aerobic exercise only (k=11) [ 32 , 34 – 38 , 40 , 44 , 49 , 50 , 53 ], followed by exercise programs combining aerobic, strengthening, balance and flexibility exercises (k=8) [ 33 , 39 , 42 , 43 , 45 48 , 55 ], and Tai Chi (k=2) [ 41 , 51 ] or resistance training only (k=2) [ 52 , 54 ]. The duration of the exercise therapy varied from 1 to 26 weeks with a median (interquartile range (IQR)) of 12 weeks (12 to 16).…”
Section: Resultsmentioning
confidence: 99%
“…et al, 2020). Previous reviews have demonstrated its effectiveness mainly on psychological issues or the overall well-being of various populations (Lee et al, 2009;Wang et al, 2010, Wang et al, 2020Schleicher et al, 2012;Lyu et al, 2018;Tong et al, 2018;Winser et al, 2018;Cheng et al, 2019;Leung et al, 2019;Zhong et al, 2020;Huang et al, 2021;Yang et al, 2021). There is no doubt that there is a lack of convincing evidence to estimate if Taichi is helpful for the physical and psychological health of college students and for students and physical education teachers to be well-informed of such benefits.…”
Section: Introductionmentioning
confidence: 99%